The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2006
DOI: 10.1523/jneurosci.3432-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Process-Localized mRNAs from Cultured Rodent Hippocampal Neurons

Abstract: The regulated translation of localized mRNAs in neurons provides a mechanism for spatially restricting gene expression in a synapsespecific manner. To identify the population of mRNAs present in distal neuronal processes of rodent hippocampal neurons, we grew neurons on polycarbonate filters etched with 3 m pores. Although the neuronal cell bodies remained on the top surface of the filters, dendrites, axons, and glial processes penetrated through the pores to grow along the bottom surface of the membrane where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
197
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(211 citation statements)
references
References 66 publications
(78 reference statements)
13
197
1
Order By: Relevance
“…We also established that Actg1 mRNA is present in mRNP granules that are immunoprecipitated with antibodies against either TRIM3 or PURA. Actg1 mRNA lacks the zip code sequence that is known to target Actb mRNA to dendrites (Eom et al, 2003;Poon et al, 2006). However, a recent deep sequencing study showed that both Actg1 and Actb transcript are identified with high confidence as dendritic/axonal transcripts in the hippocampal neuropil (Cajigas et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We also established that Actg1 mRNA is present in mRNP granules that are immunoprecipitated with antibodies against either TRIM3 or PURA. Actg1 mRNA lacks the zip code sequence that is known to target Actb mRNA to dendrites (Eom et al, 2003;Poon et al, 2006). However, a recent deep sequencing study showed that both Actg1 and Actb transcript are identified with high confidence as dendritic/axonal transcripts in the hippocampal neuropil (Cajigas et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…88,89 In fact, TOP mRNAs represent some of the most abundant transcripts localized within these structures. 90,91 While it seems unlikely that new ribosomes are assembled in this compartment, as this process is thought to strictly occur in the nucleolus, 92 the translation of TOP mRNAs may serve to selectively replace or replete translation factors and ribosomal proteins during times of increased demand in protein synthesis. 78 Another possibility is that certain elongation factors encoded by TOP mRNAs may be present in dendrites and axons in limiting amounts, such that increasing their expression by promoting TOP mRNA translation would significantly increase overall translation rates.…”
Section: Local Translation Of Top Mrnas In Activitydependent Protein mentioning
confidence: 99%
“…In the brain, local protein synthesis is critical to the development and experience-driven refinement of neural circuits, playing roles in axon guidance, synaptogenesis, and synaptic plasticity (1,2). A large but select population of transcripts localizes to axons and dendrites (3)(4)(5)(6)(7)(8), indicating that local translation subserves diverse cell biological functions. Where studied, the localization of mRNAs to axons or dendrites has been shown to depend on cisacting localization elements (LEs) usually found in the 3′ UTR, although occasionally present in the coding sequence or 5′ UTR (1,2,9).…”
mentioning
confidence: 99%